Insilico Interaction Of Selected Terpenoids Against Oral Biofilm (Streptococcus Mutans) Drug Targets. - SHIVANNI, S.S.; T, LAKSHMI. (The journal of contemporary issues in business and government, 2021)
Aim: The aim is to analyse the In Silico interaction of selected terpenoids against streptococcus mutans drug targets. Materials And Methods: • Retrieval of protein using ligand structure. Molecular docking using Results: From this study it is evident that docking is significant in Neptalactone. It has the highest fitness (-48.4), lowest VDW (-32.02), and H bond equal to standard inhibitor (- 16.33). Conclusion: The compound Neptalactone with the highest docking score is most efficient in blocking biofilm formation when compared to other compounds.